The Role of Mosques in Religious Development of the Serawai Tribe in South Bengkulu: Cultural Da'wah Approach - Indah Masruroh (Jurnal Dakwah, 2024)
This study examines mosques' role in religious development among the Serawai ethnic group in South Bengkulu through a cultural da'wah approach. The scope includes religious activities, integration of Islamic values with local customs, and community responses to culturally accommodating da'wah programs. The method employed is a qualitative ethnographic design involving participatory observation, in-depth interviews with religious and traditional leaders, and document analysis related to mosque activities. Findings reveal that mosques function as centers for religious education as well as agents of socio-cultural transformation, successfully integrating Islamic values with Serawai traditions harmoniously. The cultural da'wah approach uses traditional arts and local language to enhance youth engagement in religious activities. The main conclusion states that successful religious development among the Serawai depends heavily on the mosque's ability to adapt its da'wah methods to local cultural contexts without compromising Islamic principles.